You had me at happy hour - Janovsky, Timothy (Afterglow Books, 2024)
"O' little town of Bethlehem, Pennsylvania--it may be charming, but Julien Boire can't wait to get out of there. Soon he'll be leaving to take an advanced wine course that will put him on track to become a master sommelier. Meantime, his OCD demands he keep clear of distractions, especially the hot new hire at his aunt and uncle's restaurant, Martin's Place. Which should be easy, because Greg Harlow is as ill-suited to Julien as a bold cabernet is to a delicate salmon entrée. Charismatic and confident, Greg is a TikTok mixologist who could charm a paper bag--even one as tightly wound as Julien. One thing they do have in common: neither wants a relationship. Greg's history with dating is ... complicated. Yet working together isn't. First, they're teaming up to launch a series of happy hour events at Martin's Place. Then they're agreeing to a no-strings sex pact that involves new worlds of experimentation. Nothing is off-limits. Except a future. It's exactly how Julien wants it. Except for the little part of him that wonders if maybe he's about to lose the kind of happy that could last much longer than an hour ..." --